PENINGKATAN KETERAMPILAN TENAGA KERJA PENANGANAN KHUSUS DOKUMEN EKSPOR - Nasrullah Nasrullah; Tri Mulyani (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2016)
High competitive international trade is a key factor to find out the economic prosperity of a country. PT. APL Logistics, a private company which is dealing with delivery and logistics outside and inside Indonesia, pays closely attention of the employees’ skills. This research is using quantitative descriptive to find out the employees’ skills of PT. APL Logistics. Based on the data evaluation and library research, the result shows that 14.7 % of employees have not reach the maximum skills while 83.3 % of employees are reaching good quality. The scoring is based on three criteria; technical skills, individual skills, and individual skills which is considered not optimal.